Strategizing in the context of opportunities - Sus Aleksandra (Management, 2016)
This article attempts to draw attention to exploiting opportunities by strategists. The paper consists of four parts. The first one introduces the reader to the strategizing approach and macro and micro-level strategic analysis. The second part presents opportunities and their sources, as a background for further considerations. The third part of the article concentrates on individual characteristics of strategic management practitioners, actively identifying new opportunities. The final part focuses on the issues of behavioural uncertainty, and so this type of uncertainty, which inhibits the process of using the opportunities by strategists.